The Arabidopsis leaf provascular cell transcriptome is enriched in genes with roles in vein patterning. (26th February 2013) - Gandotra, Neeru; Coughlan, Sean J.; Nelson, Timothy
Summary Several classes of genes have been associated, by mutant phenotypes or cell biology, with the formation of vein patterns during early leaf development, including genes for certain transcription factors, auxin transport and response factors, endomembrane traffic components and other signaling pathway components. The majority of these are expressed with spatial and temporal specificity that includes expression in the precursors of vascular cells – provascular (PV) and procambial (PC) cells – suggesting that other PV/PC‐specific genes might have roles in vein patterning. We inventoried the PV/PC transcriptome of Arabidopsis leaves using a combination of laser microdissection and microarray expression profiling, and determined the phenotypes of knock‐outs of previously uncharacterized PV/PC‐specific genes. As examples, we observed vein pattern defects in knock‐out lines of KEG and a CCCH zinc finger protein. This strategy of gene discovery, based on the identification of a gene set co‐expressed in the same cells during the targeted developmental event, appears to be an efficient means of identifying genes functionally relevant to the event. In the case of vein patterning, this strategy would have identified many or most of the genes previously obtained by labor‐intensive screening for pattern‐defective mutants.